2011
DOI: 10.4049/jimmunol.1101602
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Phosphoinositide 3-Kinase δ Activity Is a Frequent Event in Systemic Lupus Erythematosus That Confers Resistance to Activation-Induced T Cell Death

Abstract: Systemic lupus erythematosus (SLE) is a human chronic inflammatory disease caused by the action of autoreactive T and B cells. Class I phosphoinositide-3-kinases (PI3K) are enzymes that trigger formation of 3-poly-phosphoinositides that induce cell survival. Enhanced PI3K activation is a frequent event in human cancer. Nonetheless, in a genetic model with enhanced activation of class IA PI3K in T cells, mice show a greater tumor index but die of a lupus-like disease. In this study, we studied the potential PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 48 publications
(94 reference statements)
1
50
0
Order By: Relevance
“…Inhibition or deletion of p110g in lupusprone mice alleviates disease symptoms (34,35), suggesting that this isoform might be useful for SLE treatment. Study of the PI3K pathway in SLE patient peripheral blood cells nonetheless showed that p110d is the isoform most frequently activated in human patients (36). The consequences of p110d inhibition for lupus development in vivo are incompletely understood.…”
Section: S Ystemic Lupus Erythematosus (Sle) Is a Complex Multigenic mentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition or deletion of p110g in lupusprone mice alleviates disease symptoms (34,35), suggesting that this isoform might be useful for SLE treatment. Study of the PI3K pathway in SLE patient peripheral blood cells nonetheless showed that p110d is the isoform most frequently activated in human patients (36). The consequences of p110d inhibition for lupus development in vivo are incompletely understood.…”
Section: S Ystemic Lupus Erythematosus (Sle) Is a Complex Multigenic mentioning
confidence: 99%
“…These analyses showed that p110d inhibition in MRL/lpr mice tends to reduce total B and T cell numbers as well as the percentages of CD4 + effector memory, and Tregs. More than 50% of human SLE patients show enhanced p110d activation in T cells and defective activation-induced cell death (AICD) (36). p110d inhibition corrected the AICD defect of SLE patient T cells in vitro (36), suggesting that p110d enhances activated and/or memory T cell survival and promotes T and B cell accumulation in SLE.…”
Section: P110d Inhibition Diminish Lupus Disease In Mrl/lpr Micementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies support the role of PTEN-and PI3K-signaling pathways in the pathogenesis of SLE and RA (17,18). Decreased PTEN mRNA expression has been described in synovial fibroblasts from RA patients and activation of Akt-1 suppresses apoptosis in synoviocytes, and promotes cell survival and disease progression.…”
Section: Discussionmentioning
confidence: 87%
“…Our group together with other groups has demonstrated that increased PI3K/Akt activation in SLE patients, both in T cells and B cells [95,96]. And PI3K (p110 containing PI3K complex) plays an important role in B cell differentiation and function, regulating class switch recombination and AID [97,98].…”
Section: Intracellular Signal Transduction In B Cellsmentioning
confidence: 99%